Identifying Plasmodium falciparum merozoite surface protein-10 human erythrocyte specific binding regions (2005)
Receptor-ligand interactions between synthetic peptides and normal human erythrocytes were studied to determine P. falciparum merozoite surface protein-10 (MSP-10) regions specifically binding to membrane surface receptors on human erythrocytes. Three MSP-10 protein High Activity Binding Peptides (HABPs) were identified, whose binding to erythrocytes became saturable and sensitive on being treated with neuraminidase, trypsin and chymotrypsin. Some of them specifically recognised a 50 kDa erythrocyte membrane protein. Some HABPs inhibited in vitro P. falciparum merozoite invasion of erythrocytes by 70%, suggesting that MSP-10 protein’s possible role in the invasion process probably functions by using similar mechanisms to those described for other MSP family antigens. In addition to above results, the high homology in amino-acid sequence and superimposition of both MSP-10, MSP-8 and MSP-1 EGF-like domains and HABPs 31132, 26373 and 5501 suggest that tridimensional structure could be playing an important role in the invasion process and in designing synthetic multi-stage anti-malarial vaccines.